直升机传动系统健康管理技术 - 蔡显新; 郭小军; 龙海跃 (Jixie chuandong)
Health management techniques using in a helicopter transmission system（THM） are presented,the technology using in the system including outline of the system,frame of the system and the procedures of the damage prediction are introduced.The improvement scheme of the system is proposed and investigated.THM system is applied and demonstrated on a helicopter transmission system,and play an important role for the transmission system passing test flight.